Clinical characteristics and chest computed tomography findings of smear-positive and smear-negative pulmonary tuberculosis in hospitalized adult patients. Issue 34 (August 2019) - Kim, Jong Hun; Kim, Min Ja; Ham, Soo-Youn
Abstract : Abstract: Pulmonary tuberculosis (PTB) continues to be one of the significant public health threats with significant morbidity and mortality. The present study was aimed to assess the clinical characteristics and chest computed tomography (CT) findings of smear-positive and smear-negative PTB in hospitalized adult patients. Hospitalized adult patients diagnosed with PTB by positive Mycobacterium tuberculosis growth on acid-fast bacilli culture from bronchial aspiration or sputum from 2015 to 2017 were reviewed. Only the patients who had chest CT within 14 days of the diagnosis of PTB were included. Medical records and CT images were analyzed. A total of 189 patients was enrolled. The median age was 62 years, and there were 118 males (62.4%). More than half of the patients had underlying chronic medical conditions (55.5%). The most common CT finding was nodular lesions (96.8%). The patients were categorized in 2 groups of smear-positive (n = 94, 49.7%) and smear-negative (n = 95, 50.3%). Between 2 groups, there was no difference in underlying medical conditions. However, there were more lesions of cavity, consolidation, bronchiectasis, upper lobe involvement, multiple lobe involvement, and lymphadenopathy in the smear-positive group. A predictive model for smear-positive tuberculosis was created based on the comparison analysis that had an area of 0.724 under the receiver operating characteristic curve. In a multivariate logistic regression analysis, CT findings of consolidation (odds ratio [OR] 2.521, 95% confidence interval [CI] 1.175–5.408, P  = .02), lymphadenopathy (OR 1.947, 95% CI 1.025–3.696, P  = .04), and multi-lobe involvement (OR 2.795, 95% CI 1.084–7.205, P  = .03) were associated with smear-positive PTB. PTB patients who have chest CT findings of cavity, consolidation, bronchiectasis, upper lobe involvement, multiple lobe involvement, and lymphadenopathy may be at higher risk for smear-positive TB. A predictive model may be helpful for further assessment.